UPAYA MENINGKATKAN HALAL ADOPTION PADA TENUN SONGKET ETNIK LOKAL PANDAI SIKEK - Resti Purnama Dewi; Ratni Prima Lita; Suziana; Meuthia; Dewi Yuliana Rahmi; Laura Amelia Triani (Halu Oleo University, 2024)
The rapid transition of the global halal fashion industry may require a series of innovations and adaptations in the MSMEs sector. Therefore, technology adoption and organizational openness to change are the main challenges for stakeholders. This study was conducted to examine and analyze the effects of technology, organization, and an increasingly competitive environment on halal adoption in the MSME weaving sector. By using a purposive sampling technique with certain criteria, as many as 30 MSMEs owners or members were obtained to contribute and respond to the research questionnaire, and then those responses were analyzed through the Structural equation model technique with Smart-PLS software's latest version. Results stated that halal adoption in the MSMEs weaving sector is not affected by technological and organizational aspects, it is due to a lack of openness to accept the changes, then most of the actors also thought that halal adoption didn’t provide value-added. Therefore, the motivation for human resource development and technology utilization was also low. Halal adoption is significantly affected by environmental aspects. External pressures such as market demand and government regulations will force weaving MSME actors to adapt to the changes for business sustainability and maintaining national fashion cultural heritage.